Experiences of postpartum women during the Covid-19 pandemic (Research, Society and Development, 2025)
The gestational period is widely known for bringing about numerous changes in a woman's body, both physical and emotional. These transformations, often accompanied by fear, anguish and anxiety, can be intensified or alleviated by the quality of the relationship between the mother, the baby and the support network, which play an essential role in this process. This research, with a qualitative approach, was conducted throughout 2023, through semi-structured interviews to better direct the theme, and focused on a group of women who experienced the gestational period or the postpartum period during the COVID-19 pandemic (2020-2023). The objective was to explore the feelings of postpartum women in the postpartum period, considering the challenges imposed by the need for social isolation to control the virus, in addition to discussing the difficulties they faced in this context. The study in question identified that as the pregnancy progressed and prenatal consultations became more frequent, the greatest fear was being without adequate health services for the necessary care such as exams and vaccinations for the new being.